Authentic Oral Interaction in the EFL Class: What It Means, What It Does not - José David Herazo Rivera (Universidad Nacional de Colombia, 2010)
The communicative approach in EFL education has generated a concern for the development of communication in the foreign language classroom within which the promotion of oral interaction is usually paramount. However, what constitutes authentic oral interaction is sometimes not clearly understood and some of the activities that take place in the classroom seem unlikely to generate meaningful opportunities for the development of oral interaction. To address this gap, this paper characterizes four samples of oral communication exchanges that occur in Colombian EFL secondary school classrooms in Monteria and discusses their effectiveness for developing meaningful oral production in both student-student and teacher-student interaction. The paper has two main sections: the first is devoted to the analysis of student-student interaction, and the second to discussing teacherstudent exchanges.